Reconceptualising inquiry in science education. Issue 1 (2nd January 2016) - Bevins, Stuart; Price, Gareth
ABSTRACT: Decades of discussion and debate about how science is most effectively taught and learned have resulted in a number of similar but competing inquiry models. These aim to develop students learning of science through approaches which reflect the authenticity of science as practiced by professional scientists while being practical and manageable within the school context. This paper offers a collection of our current reflections and suggestions concerning inquiry and its place in science education. We suggest that many of the current models of inquiry are too limited in their vision concerning themselves, almost exclusively, with producing a scaffold which reduces the complex process of inquiry into an algorithmic approach based around a sequence of relatively simple steps. We argue that this restricts students' experience of authentic inquiry to make classroom management and assessment procedures easier. We then speculate that a more integrated approach is required through an alternative inquiry model that depends on three dimensions (conceptual, procedural and personal) and we propose that it will be more likely to promote effective learning and a willingness to engage in inquiry across all facets of a students' school career and beyond.